The growth of entrepreneurial human capital: origins and development of skill variety - Alexander Krieger; Michael Stuetzer; Martin Obschonka; Katariina Salmela-Aro (Small Business Economics, 2021)
Given that recent research on entrepreneurial behavior and success has established skill variety as a central human capital factor, researchers, educators, and policymakers have turned their interest to a deeper understanding of the formation of skill variety. Based on human capital theory and the competence growth approach in developmental psychology (highlighting long-term, age-appropriate, and cumulative skill-growth processes), we hypothesize that a broad, early variety orientation in adolescence is a developmental precursor of such entrepreneurial human capital in adulthood. This was confirmed in an analysis of prospective longitudinal data via structural equation modeling and serial mediation tests. We also find that an entrepreneurial constellation of personality traits, but not entrepreneurial parents, predicts early variety orientation, skill variety, and entrepreneurial intentions. By shedding new light on the long-term formation of entrepreneurial human capital, the results suggest that establishing and benefiting from an early variety orientation is not only an important developmental mechanism in entrepreneurial careers but gives those with an entrepreneurial personality an early head start in their vocational entrepreneurial development. Implications for future research and practice are discussed.
Keywords: J24; L26; M13; 330; Skill variety; Early variety orientation in adolescence; Entrepreneurial intentions; Entrepreneurial Big Five profile; Entrepreneurial role models